2018
DOI: 10.1177/1350506818802425
|View full text |Cite
|
Sign up to set email alerts
|

Economic violence against women: Testimonies from the Women’s Court in Sarajevo

Abstract: This article uses a feminist political economy framework to analyse economic violence against women in the context of the violent disintegration of Yugoslavia and the introduction of neoliberal regimes in its successor states from the late 1980s until 2015. The authors’ focus is on the following processes before, during and after the breakup: the wider social, political and economic context of Yugoslavia before the war, already marked by the introduction of orthodox neoliberal standards and practices and combi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Nationalistic ideologies overemphasised the notion of ‘home’ as much as ‘homeland’. Men were entrusted with the roles of protectors and breadwinners, irrespective of the actual impossibility to achieve this model due to the socio-economic transformation (privatisation with worker lay-offs, increased joblessness, reduced earnings and labour protections, disappearance of employment benefits such as health, transport, holiday and sick-leaves) and a consequent crisis of masculinity (Đurić Kuzmanović and Pajvančić Cizelj, 2020). It is relevant to stress here that during socialist times – due to economic necessities – both husband and wife were often employed, so the sole male-breadwinner model was seldom the reality of families under socialist regimes (Milić, 1993).…”
Section: Serbia and War Widows In The Aftermath Of The Wars In The 1990smentioning
confidence: 99%
“…Nationalistic ideologies overemphasised the notion of ‘home’ as much as ‘homeland’. Men were entrusted with the roles of protectors and breadwinners, irrespective of the actual impossibility to achieve this model due to the socio-economic transformation (privatisation with worker lay-offs, increased joblessness, reduced earnings and labour protections, disappearance of employment benefits such as health, transport, holiday and sick-leaves) and a consequent crisis of masculinity (Đurić Kuzmanović and Pajvančić Cizelj, 2020). It is relevant to stress here that during socialist times – due to economic necessities – both husband and wife were often employed, so the sole male-breadwinner model was seldom the reality of families under socialist regimes (Milić, 1993).…”
Section: Serbia and War Widows In The Aftermath Of The Wars In The 1990smentioning
confidence: 99%
“…Among non-physical types of violence, economic violence, despite its potential significance, has not been adequately studied globally. Until now, limited empirical research has been conducted on the links and consequences of economic violence [ 4 , 18 , 25 , 39 , 57 ]. In recent years scales have been developed, tested and revised by scholars to measure economic violence [ 5 , 17 19 , 22 24 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Another study also showed remarkable results. It points to the conclusion that the intersection of Orthodox neoliberal politics and privatization with patriarchy, nationalism and conflict encouraged economic violence against women in the region [ 57 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…While the women's movement in post-war Bosnia has organized around women's extraordinary resilience and self-sufficiency in the wake of sexual and genderbased violence (Björkdahl 2012;Helms 2013), their economic precarity and continuing vulnerability has received less attention. A lack of secure and well-paid jobswhich results from the broader socio-economic climate and state dysfunction, analyzed in the previous sectionunderscores women's dependence on male breadwinners and subjects them to a normalization of gender-based violence (Jelin-Dizdar 2012; Đurić Kuzmanović and Pajvančić-Cizelj 2018). This is reinforced by women's exclusion from property ownership (Mucović 2017).…”
Section: Neoliberal Reforms and Violence Against Womenmentioning
confidence: 99%